Pendampingan Pertukaran Mahasiswa Merdeka:Gama Sandya Polines - Yusuf Hendrawanto; Ana Putri Nastiti; Sri Hardiningsih H.S; Nurul Hamida; Toni Hartono; Pandiya (CV. Multi Kreasi Media, 2026)
An The Pertukaran Mahasiswa Merdeka (PMM) program is one of the flagship policies of the Merdeka Belajar–Kampus Merdeka (MBKM) initiative, aimed at broadening national insight, fostering tolerance, and strengthening students' patriotism through cross-cultural learning. This community service project aims to describe and analyze the process and outcomes of mentoring the PMM Gama Sandya group at Politeknik Negeri Semarang (Polines) in 2024. The implementation method utilized a participatory approach consisting of planning and potential mapping stages, the execution of 19 Modul Nusantara activities, and monitoring and evaluation based on Kirkpatrick’s four-level model. The mentoring results demonstrate that the Gama Sandya group successfully completed all targeted activities, which included: 10 diversity activities (visits to historical sites, places of worship, museums, and economic centers), 6 reflection activities (sharing sessions, interfaith fast-breaking, and bonding gatherings), 2 inspiration activities (livestock farming study at Propang Akmil and the Carica Gemilang MSME), and 1 social contribution activity (beach cleanup and staple food distribution at Sundak Beach, Gunungkidul). This structured mentoring proved effective in accelerating students' socio-cultural adaptation, reducing intercultural prejudice, and strengthening a shared national identity among exchange students.